Attitude of Social Media Users to Internet Advertising - Patricia E, CHIOMA; Ifedolapo, OMONIYI; Ernest E, ONUIRI (IJRDO-Journal of Applied Science, 2016)
The pervasiveness and wide use of social media has become a global phenomenon and has since become a viable tool in promoting products and brands. It is in view of this that this research seeks to ascertain the attitude of social media users to Internet advertising. The adopted methodology is the descriptive survey with the target audience being college students of Covenant University, a privately owned faith-based institution of higher learning in Southwest Nigeria. Results obtained showed that 100% of the social media users have knowledge of Internet Advertising whereas 71.8% of the respondents actually pay attention to the Internet adverts, hence suggesting that the Internet can be a good tool for brand promotion. Findings also reveal that 73% of respondents have at some point altered their purchase decision due to various adverts they have been exposed to on the Internet.